Inventory and credit decisions under day-terms credit and stock-dependent demand. (2017) - Aggarwal, K.K.; Tyagi, Arun Kumar
Selling on credit is used by the firm as a marketing strategy to stimulate their demand. Credit period through its influence on demand becomes a determinant of inventory decision and inventory sold on credit-terms gets converted to accounts receivable. Hence, inventory and credit-terms decisions are interrelated which should be coordinated and determined simultaneously. Moreover, in addition to credit period the inventory-levels would also have a stimulating effect on demand. Thus, in an inventory system with credit-linked demand the impact of stock-dependent demand phenomenon which arises naturally due to customers' psychology must also be considered in order to obtain optimal inventory and credit granting decisions. Consequently, in this article, a mathematical model is developed to jointly determine optimal inventory and credit decisions in an inventory system when demand is dependent on day-terms credit period as well as on instantaneous inventory-level. The model is developed using discounted cash flow approach and the objective is to maximise the present value of net profit per unit time. Finally, numerical example and sensitivity analysis have been presented to illustrate the effectiveness of the proposed model.